Invisible Emmie - Libenson, Terri (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2017)
All the crushes, humiliations, boredom, and drama of middle school are compressed into one surprising day when an embarrassing note falls into the wrong hands.
Keywords: Middle school -- Juvenile fiction; Letters -- Juvenile fiction; Graphic novels